The Effect of Learning Experience Using Multimedia on the Ability in the Language of Meaning Kindergarten 2nd Year - Sukkasem, Sumitra (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The objectives of this research were: To measure and compare the communication skills of students before/after the study; o explore the overall level of abilities for communication of students compared to the 85 percent criterion. The sample group consisted of 23 students from Kindergarten Grade 2 at Anuban Tambon Khok Samrong School in the academic year 2022, semester 1 - 2. The samples were selected by purposive sampling method. The instruments used in the study consisted of 14-unit multimedia materials enhancing communicative language skills, a Language Skills and Abilities for Communication Test, which is a 40-item 3-choice multiple questions with the 4-section 10-item practice test. Statistics used for analysis were percentage, mean, standard deviation, and a hypothesis test (t-test). The results showed that 1. After the study, students have a higher level of interpretive language ability, statistically significant at the .05 level. 2 The level of communication ability of Kindergarten 2 students is higher than the 85 percent criterion, which is statistically significant at the .05 level.